Phosphodiesterase inhibitors for treatment of voiding dysfunction : an overview of experimental and clinical evidence - Reges, Ricardo (2014)
Recently, the focus of the origin of lower urinary tract symptoms (LUTS) has change from the prostate to the bladder. Regardless of the underlying mechanism associated with the origin of LUTS, alpha-blockers continue to be the most common medicine prescribed to treat LUTS due to benign prostatic obstruction (BPO). The newest class of drug introduced to treat LUTS/BPO is phosphodiesterase inhibitors (PDEi) and the aim of this study was to review the role of PDEi in the treatment of LUTS/BPO. In this review, the first evidence was evaluated based on epidemiological studies followed by randomized clinical trials which provide evidence on the administration of PDEi in patients with LUTS/BPO. Experimental studies were also assessed to tentatively elucidate the association between LUTS and erectile dysfunction, and to elucidate the underlying mechanism. There is still controversy regarding the administration of PDEi due to the fear of detrusor impairment, response to acute administration, and the effects of PDEi combined with alpha-blockers. Following this review, we conclude that treatment of BPO/LUTS with PDEi is beneficial, based on experimental studies, strong evidence and the large number of randomized clinical trials confirming their efficiency.